Microbial fuel cells using mixed cultures of wastewater for electricity generation - Zain .S.M,; Roslani .N.S,; Hashim .R,; Anuar .N,; Suja .N.F,; Daud .W.R.W,; Basri .N.E.A, (Universiti Kebangsaan Malaysia, 2011)
Fossil fuels (petroleum, natural gas and coal) are the main resources for generating electricity. However, they have been major contributors to environmental problems. One potential alternative to explore is the use of microbial fuel cells (MFCs), which generate electricity using microorganisms. MFCs uses catalytic reactions activated by microorganisms to convert energy preserved in the chemical bonds between organic molecules into electrical energy. MFC has the ability to generate electricity during the wastewater treatment process while simultaneously treating the pollutants. This study investigated the potential of using different types of mixed cultures (raw sewage, mixed liquor from the aeration tank & return waste activated sludge) from an activated sludge treatment plant in MFCs for electricity generation and pollutant removals (COD & total kjeldahl nitrogen, TKN). The MFC in this study was designed as a dual-chambered system, in which the chambers were separated by a NafionTM membrane using a mixed culture of wastewater as a biocatalyst. The maximum power density generated using activated sludge was 9.053 mW/cm2, with 26.8% COD removal and 40% TKN removal. It is demonstrated that MFC offers great potential to optimize power generation using mixed cultures of wastewater.